Minimally Invasive Hysterectomy and Bariatric Surgery to Improve Endometrial Cancer Survivorship. Issue 3 (September 2019) - Shafa, Anousheh; Kumar, Amanika; Torres, Diogo; McKenzie, Travis J.
Abstract : BACKGROUND: Surgery is curative for the majority of early-stage endometrial cancers. Postoperatively, patients are actually at much higher risk of mortality from obesity-related comorbidities unless they have sustained weight loss. CASE: A 54-year-old woman with class III obesity, type II diabetes mellitus complicated by neuropathy and retinopathy, hypertension, sleep apnea, and fatty liver disease was diagnosed with grade 1 endometrioid uterine cancer. She underwent dual surgery with laparoscopic bariatric surgery and robotic-assisted laparoscopic hysterectomy. The perioperative period was uncomplicated, and final pathology was consistent with a stage IA grade 1 endometrial cancer. In 12 months, the patient lost 41.3 kg and required less insulin, metformin, and antihypertensive medication. CONCLUSION: Combined minimally invasive hysterectomy and bariatric surgery for obese women with endometrial cancer can promote sustained weight loss and improve survivorship. Abstract : Dual minimally invasive hysterectomy and bariatric surgery for endometrial cancer may promote sustained weight loss and improve survivorship.